Why do some entrepreneurs succeed and others failed? The Timmons framework - A. Rahman, Badruddin; Mohd Shariff, Mohd Noor (ASEAN Universities Consortium of Entrepreneurship Education (AUCEE), 2010)
Successful entrepreneurs share common attitudes and behaviors. They possess not only a creative and innovative flair, but also solid general management skills, business know-how, and sufficient contact. Some other failed attributing to mainly incompetence. These entrepreneurs do not know how to run the enterprise. They make major mistakes that an experienced, well-trained entrepreneur would quickly see and usually sidestep. In tying to explain this phenomenon, Timmons develops a framework relating the driving forces that dominate the entrepreneurial process. The Timmons model incorporates the following aspects: (a) It is opportunity driven; (b)It is driven by a lead entrepreneur and an entrepreneurial team; (c) It is resource parsimonious and creative; (d) It depends on the fit and balance among these; and (e) It is integrated and holistic.